A critical examination of the learning environment related to science in 9-11 year classes in the schools of Sri Lanka - Devendra, S.P. (My University, 1999)
Sri Lanka, as a developing country has identified the necessity to depend on science education to meet the needs of scientific and technological manpower for rapid development. In Sri Lanka a common curriculum with science for all in the grade 6-11was implemented in the year 1972. This was a hasty implementation, the government made after facing the insurrection....